Pengaruh Spiritualitas di Tempat Kerja Pada Kinerja Karyawan Yang Dimediasi Perilaku Kewargaan Organisasi, Dan Kecerdasan Emosional Sebagai Variabel Moderasi (Studi di RSJD Dr. RM. Soedjarwadi) - Bagus Ananta Pratidina; Ismi Darmastuti; Aulia Vidya Almadana (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyse the effect of spirituality in the workplace, with a mediating role by organisational citizenship behaviour, and a moderating role by emotional intelligence in improving employee (nurse) performance. In addition, the inconsistency of previous research is the reason this research was conducted. The population used in this study were all active nurses at RSJD Dr. RM. Soedjarwadi, Klaten. The number of samples used in this study were 74 respondents. The data collection method was carried out through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis technique with SMART PLS 3 analysis tool. The results of this study indicate that by including spirituality in the workplace positively and significantly affects employee performance, and emotional intelligence strengthens the influence of spirituality in the workplace on employee performance. Meanwhile, the role of organisational citizenship behaviour has no effect on employee performance. It can be concluded that hypotheses one and two have a positive and significant effect, and hypothesis four strengthens the influence between spirituality in the workplace on employee performance. While hypothesis three has no effect on improving employee performance